Perancangan Sistem Informasi Badan Kerjasama Antar Desa UPK Simpan Pinjam Berbasis Website Kecamatan Somagede - Dwi Hamdani Adiatma Budhie; Eka Rini Yulia (Computer Science (CO-SCIENCE), 2022)
The Inter-Village Cooperation Agency or BKAD which is a business forum formed based on an agreement between villages. After doing research at the BKAD, Somagede District, Savings and Loans Management Unit, the problem that occurs is that the use of technology has not been maximized and the system used in the recording process is still using books. In terms of data storage and retrieval will be difficult. Efforts to manage human resources and natural resources around so as to increase village income. From these problems, the website-based BKAD UPK Savings and Loan Information System was created. This study uses the method of observation, interviews and literature study, while the system development uses agile software development method with the Extreme Programming (XP) methodology. This information system is made using the Notepad++ software application as a text editor and XAMPP Version 3.3.0 as a local server which will later be given a domain and hosting. While the programming language uses PHP and HTML. With a computerized system, data collection is well structured, reducing problems that arise due to a manual system and can facilitate the work of BKAD employees in data so that it is more effective and efficient in its use.